Unfinished business : screening the Italian Mafia in the new millennium - Renga, Dana, 1971- (Toronto Italian studies., 2013)
"Unfinished Business is the first book to examine Italian mafia cinema of the past decade. It provides insightful analyses of popular films that sensationalize violence, scapegoat women, or repress the homosexuality of male protagonists. Dana Renga examines these works through the lens of gender and trauma theory to show how the films engage with the process of mourning and healing mafia-related trauma in Italy